SURGICAL TREATMENT OF AN ABNORMAL UPPER LABIAL FRENUM IN PEDIATRIC DENTISTRY: CASE REPORT - Henrique Moura Fonsêca dos Santos, Álvaro; Eduarda Pelizaro Almeida Santos, Bárbara; Gabrielly de Souza Moura, Camila; Brito de Almeida Couto, Victória; da Rocha Costa, Maurício (Health and Society, 2023)
Introduction: The superior labial frenum corresponds to a thin and triangular anatomical structure that has its formation during the third month of intrauterine life, located from the tubercle of the upper lip to the alveolar process. Abnormal insertion of the roof-labial frenulum is usually indicated for surgical removal. If the surgical procedure is not performed, the frenum causes instability, the main problem being the diastema between the incisors, which many times cannot be treated only by orthodontics. The purpose of correction of the upper labial frenum consists of eliminating excess free tissue between the teeth, in addition to the purpose of improving aesthetics. Objective: To describe a case report of surgical treatment of the upper labial frenum performed on a pediatric patient at a Dental Specialties Center. Case report: Female patient, 11 years old, referred by the orthodontist with indication for surgical treatment of the upper labial frenum. On intraoral physical examination, the presence of persistent roof-labial frenum and diastema between the upper central incisors was observed. In view of the data obtained in the anamnesis and physical examination, we opted for the frenotomy technique with the repositioning of the brake. Intraoral antisepsis and facial antisepsis were performed, followed by terminal infiltrative anesthesia in the anterior superior alveolar nerves, bilaterally. Two oblique incisions were made close to the insertion of the roof-labial frenum and then the repositioning of the. Friction movements were performed between the incisors and simple stitches were used for suturing. After two weeks, the patient returned and the presence of tissue remnant was observed, which was removed using the same anesthetic technique and with the aid of Metzenbaum scissors, without the need for a new suture. Conclusion: Surgical treatments for labial frenum present excellent results and should be chosen according to the individual needs of each patient, always evaluating the risks, benefits and advantages and disadvantages.